(untitled) (Journal of Nepal Geological Society, 2015)
The Gorkha Earthquake occurred on the gently dipping part of the Main Himalayan Thrust (MHT), close to the Main Central Thrust (MCT). This earthquake possibly occurred in the source zone of the 1833 Nepal Earthquake (Mw 7.6), which occurred after 182 years. The region between the 1905 Kangra Earthquake and 1934 Bihar-Nepal Earthquake has not produced any great earthquake since the last 500 years and still remains a potential site for great earthquake(s) in future. The Kathmandu Valley witnessed moderate ground acceleration and comparatively large velocity as recorded at Kantipath during the Mw 7.8, Gorkha Earthquake. The analysis of the records show that high frequencies were damped and low frequencies were dominant over the sedimentary basin, which can be attributed to the response of the sediments underneath. Because of damping of high frequencies, the engineered, low storey buildings were less damaged and resisted the ground shaking comparatively well. However, on the other hand, the historical monument ’Dharahara’ collapsed completely and the high rise apartment buildings suffered more because of the dominance of low frequencies.